1998
DOI: 10.1111/j.1532-950x.1998.tb00105.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical, Radiographic, and Surgical Localization of Intervertebral Disc Extrusion in Small‐Breed Dogs: A Prospective Study of 50 Cases

Abstract: Intervertebral disc extrusion in small-breed dogs frequently results in bilateral distribution of extruded material. Computed tomography or magnetic resonance imaging may be necessary to delineate completely the distribution of extruded disc material in IDE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
46
1
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 4 publications
5
46
1
5
Order By: Relevance
“…Thus our data is in agreement with past reports. The degree of neurological deficit in the TL-IVDH group included in this study almost agrees with that of a previous study, with the exception of Grade V, in that Grade V, IV, III, II and I made up 0%, 42%, 32 %, 24% and 3% of the group, respectively [24]. Other reports from the U.S.A., however, are in agreement with our data concerning Grade V, suggesting the existence of a deficit in deep pain sensation, which is defined as Grade V in our grading and which accounted for 8.1 to 10.1% [2,16,23].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Thus our data is in agreement with past reports. The degree of neurological deficit in the TL-IVDH group included in this study almost agrees with that of a previous study, with the exception of Grade V, in that Grade V, IV, III, II and I made up 0%, 42%, 32 %, 24% and 3% of the group, respectively [24]. Other reports from the U.S.A., however, are in agreement with our data concerning Grade V, suggesting the existence of a deficit in deep pain sensation, which is defined as Grade V in our grading and which accounted for 8.1 to 10.1% [2,16,23].…”
Section: Discussionsupporting
confidence: 91%
“…The grade of myelopathy in the C-IVDH group was divided into the following three categories based on neurological status according to a previous study [11] with minor modifications: grade 1, normal ambulation with neck pain; grade 2, ambulatory tetraparetic with neck pain; grade 3, nonambulatory tetraparetic. The grade of myelopathy in the TL-IVDH group was divided into the following five categories according to a previous study [24]: Grade I, spinal hyperesthesis only; Grade II, mild ataxia with motor function adequate for weight support; Grade III, severe ataxia with motor function inadequate for weight support; Grade IV, paralysis of the hind limb with intact deep pain sensation; Grade V, paralysis of the hind limb with no deep pain sensation.…”
Section: Methodsmentioning
confidence: 99%
“…However, the clinical lateralization of the herniated disc material was found to be the least reliable factor in this study for determining on which side the hemilaminectomy should be performed (31).…”
Section: Discussionmentioning
confidence: 85%
“…The accuracy of CT and myelography has been found to be similar when compared to surgical findings in chondrodystrophic dogs with intervertebral disc disease [1][2][3] . However, the use of surgical findings as a reference standard has been questioned due to a high degree of bias and limited ability to circumferentially inspect the spinal canal when performing a hemilaminectomy 6 . A prospective comparison of CT, nonselective angiographic CT, myelographic CT, and myelography in dogs with various myelopathies found that CT myelography had the highest accuracy when compared to surgical findings 5 .…”
mentioning
confidence: 99%